2010
DOI: 10.1017/s0317167100010969
|View full text |Cite
|
Sign up to set email alerts
|

Hirayama Disease

Abstract: A previously healthy 16-year-old female with no family history of neuromuscular disorders presented with a seven year history of hand incoordination. On examination, she had wasting of the intrinsic hand muscles bilaterally, right worse than left. There was no sensory loss, muscle cramping, or pain. Magnetic resonance imaging (MRI) of the cervical spine did not reveal any abnormal findings. Nerve conduction studies identified moderate slowing of the conduction velocity in the right ulnar nerve.One year later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…18 The incidence of cold paresis and tremors on finger extension reported in the literature varies from 27.3% to 97%. 3,7,11,19 Five patients (83%) in our series either gave a history of cold paresis or developed that symptom after they were examined following immersion of their hands in cold water followed by improvement after immersion in warm water. Tremor, when present, also showed similar temperature sensitivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18 The incidence of cold paresis and tremors on finger extension reported in the literature varies from 27.3% to 97%. 3,7,11,19 Five patients (83%) in our series either gave a history of cold paresis or developed that symptom after they were examined following immersion of their hands in cold water followed by improvement after immersion in warm water. Tremor, when present, also showed similar temperature sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…1 The majority of reported cases are from Asia, primarily Japan, 2 and other southern and eastern Asian countries, [3][4][5] with only a few cases from Europe [6][7][8] and North America. [9][10][11][12][13] The symptoms usually start from 1 upper limb and slowly progress to involve the same segments of the contralateral upper limb. 14 Electrodiagnostic examination showing bilateral C8, T1, and C7 segmental denervation with normal sensory nerve conduction is essential in confirming the diagnosis.…”
mentioning
confidence: 99%
“…[3][4][5][6] To date, there have only been a handful of cases reported from North America, and to our knowledge, there has been no published study characterizing the MR imaging features of this disease in North American patients. [7][8][9][10][11] MR imaging findings reported in patients from Southeast Asia and Japan include LOA of the dura to the lamina, asymmetric lower cervical spinal cord atrophy, spinal cord T2 hyperintensity, loss of cervical lordosis in the neutral position, and forward displacement of the dura with flexion MR imaging. 8 In our experience, HD may be more common in North America than the current literature indicates.…”
mentioning
confidence: 99%
“…As a consequence, neck flexion causes detachment of the tight dura from its posterior anchor and the dura falls forward and causes abutment of the spinal cord against the anterior vertebral column. 1,4,8 Additionally, neck flexion in HD patients results in dysfunction of anterior horn cells, as has been recently demonstrated in a study of 38 HD patients showing an increased number of repeater F-waves during neck flexion. 9 The authors concluded that HD patients should avoid neck flexion for a long period of time.…”
Section: Discussionmentioning
confidence: 70%
“…However, the early onset in a female, as in our case, has rarely been reported. [2][3][4] Concerning the etiology, it was proposed that a disproportionate growth of the vertebral column and the contents of the spinal canal during the juvenile growth spurt cause HD and the peak of the histogram for onset age is approximately 2 years later than the peak of growth curve. 1 So far, however, this theory remains to be proven.…”
Section: Discussionmentioning
confidence: 99%